RITUAL OF CHRISTMAS EVE SUPPER IN THE OPOCZNO REGION. TRADITION AND THE PRESENT DAY - Kupisiński, Zdzisław (Forum Teologiczne, 2023)
This article presents the customs, rituals and beliefs of the Christmas Eve supper in the Opoczno subregion, both those practiced at the beginning of the 20th century and those that have survived to the present day. To address the problem at hand, the author has used his own factual material, collected during ethnographic field research conducted in Opoczno in 1990–1993, as well as the literature on the subject. The author’s intention is not only to present the preparations for the Christmas Eve feast and its course but also to show the customs and rituals of this day and supper as rites of passage according to the theories of Arnold van Gennep. These rituals assume three phases: preliminal, liminal and postliminal. In the first phase, a break is made with the previous reality and everyday life in order to enter a state of suspension, i.e. a transitional state, and after performing the rituals specified by tradition, to reach a new reality. The realization of rites of passage can be seen in the inner experiences of the participants at the Christmas Eve feast, which has a religious character.